Cycling, Fuel Discount and the 9 exteuro Ticket: Commuters Taking a Brake? - Franziska Harter (Universität Rostock, Wirtschafts- und Sozialwissenschaftliche Fakultät, Institut für Volkswirtschaftslehre, 2023)
Does the promotion of public transport crowd out other modes of climate friendly mobility? During the summer of 2022, Germany introduced two policy measures to countervail the rising cost of living and energy. This paper demonstrates that these measures did not only affect individuals relying on motorized mobility but cyclists as well. Employing publicly available data from urban bike counters and data from city administrations, I find that the number of trips commuted by bicycle significantly decreased on average by 20 rides per hour and station. Moreover, I find lasting impacts after the withdrawal that indicate that the pre-intervention trend reverted.
Keywords: 330; mobility; bike counter; policy intervention; interrupted time-series